A meta-analysis of the relationship between social support and physical activity in adolescents: the mediating role of self-efficacy - Lin, Hao; Chen, Haidong; Liu, Qingzao; Xu, Jie; Li, Shan (Frontiers in Psychology, 2024)
Introduction: Social support influences physical activity (PA) in adolescents. However, whether or not mediating and moderating effects impact the relationship between them or the underlying mechanism remains unclear. This study aimed to investigate the mediating effects of self-efficacy as well as a series of moderating influences using a meta-analytic approach. Methods: A total of 56 studies published between January 2001 and May 2023 were obtained from Web of Science, EBSCO, Taylor & Francis, Scopus, Wiley, ProQuest, and CNKI (core) databases, containing 65 independent samples (total sample size = 47,196). Results and discussion: The mean weighted correlation coefficients between social, family, peer, and school support and adolescent PA were 0.298, 0.226, 0.256, and 0.142, respectively, which were significant, except for school support. Family support and teenage PA were related, although the connection was moderated by gender and socioeconomic characteristics. While social, family, and peer support had a direct influence on adolescent PA, school support did not. Self-efficacy mediated the relationship between social support and its subtypes and adolescent PA.